1993
DOI: 10.1007/bf02096883
|View full text |Cite
|
Sign up to set email alerts
|

Higher dimensional classicalW-algebras

Abstract: Classical W -algebras in higher dimensions are constructed. This is achieved by generalizing the classical Gel'fand-Dickey brackets to the commutative limit of the ring of classical pseudodifferential operators in arbitrary dimension. These W -algebras are the Poisson structures associated with a higher dimensional version of the Khokhlov-Zabolotskaya hierarchy (dispersionless KP-hierarchy). The two dimensional case is worked out explicitly and it is shown that the role of DiffS (1) is taken by the algebra of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The brackets induced on the w j (u i ) by the above mapping coincide with those computed with J cl L p , up to a global factor p 2 [12]. It is worth noting that even for the higher dimensional generalization of the classical Gelfand-Dickey brackets that were constructed in [13] the two previous theorems hold. This is not at all obvious since, for example, this construction uses not one but two different splittings.…”
mentioning
confidence: 58%
“…The brackets induced on the w j (u i ) by the above mapping coincide with those computed with J cl L p , up to a global factor p 2 [12]. It is worth noting that even for the higher dimensional generalization of the classical Gelfand-Dickey brackets that were constructed in [13] the two previous theorems hold. This is not at all obvious since, for example, this construction uses not one but two different splittings.…”
mentioning
confidence: 58%
“…which are defined in a similar way to tensor operators (26), but replacing the angular momentum operatorsĴ (N ) by the coordinates x = (cos ϕ sin ϑ, sin ϕ sin ϑ, cos ϑ), i.e. its covariant symbols (20). Indeed, the large-N structure constants can be calculated through the scalar product (see [28]):…”
Section: Tensor Operator Algebras Of Su(2) and Large-n Matrix Modelsmentioning
confidence: 99%
“…Also, W ∞ (2, 2) was interpreted as a higher-conformal-spin extension of the diffeomorphism algebra diff(4) of vector fields on a 4-dimensional manifold (just as W ∞ is a higher-spin extension of the Virasoro diff(1) algebra), thus constituting a potential gauge guide principle towards the formulation of of induced conformal gravities (Wess-Zumino-Witten-like models) in realistic dimensions [18]. For completeness, let as say that W ∞ -algebras also appear as central extensions of the algebra of (pseudo-)differential operators on the circle [19], and higher-dimensional analogues have been constructed in that context [20]; however, we do not find a clear connection with our construction.…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional generalization 2u tx + (uu x ) x − u yy − u zz = 0 (1.3) and its symmetries were studied by Krasil'shchik, Lychagin and Vinogradov [17] (1986) and by Schwarz [25] (1987). Martinez-Moras and Ramos [18] (1993) showed that the higher dimensional classical W-algebras are the Poisson structures associated with a higher dimensional version of the Khokhlov-Zabolotskaya hierarchy. Kacdryavtsev and Sapozknikov [9] (1998) found the symmetries for a generalized Khokhlov-Zabolotskaya equation.…”
Section: Introductionmentioning
confidence: 99%